Association between metabolism and low back pain: a cross-sectional study - XingKun Wang; Long Tian; Qian Xu; Xin Pan; Lingjun Kong; Hua Zhao (Journal of Orthopaedic Surgery and Research)
Abstract Background While pervious studies have identified metabolic imbalance as a key driver of intervertebral disc degeneration, few studies explored the relationship between metabolic and low back pain directly. We aimed to explore the relationships between two critical metabolic factors—insulin resistance and obesity—and low back pain (LBP), thereby providing novel insights for the integrated management of patients with LBP. Methods We enrolled 41663 participants from four NHANES survey cycles (1999–2004 and 2009–2010). The Metabolic Score for Insulin Resistance (METS-IR) and Body Roundness Index (BRI) were utilized to investigate the associations of insulin resistance and visceral obesity with LBP.Weighted logistic regression models were constructed to evaluate associations between MetS-IR/BRI and LBP, reported as odds ratios (ORs) with 95% confidence intervals (CIs). Using Restricted Cubic Splines (RCS) to assess potential nonlinear relationships. ROC curve analysis quantified diagnostic performance through area under the curve (AUC) estimation. Subgroup analyses and interaction tests were conducted to ensure the robustness of the findings. Results Multivariable regression analysis revealed significant positive associations between MetS-IR/BRI and LBP after adjusting for all potential confounders (MetS-IR: OR = 1.013, 95% CI: 1.008–1.018; BRI: OR = 1.072, 95% CI: 1.047–1.098) and these associations remained consistent across all subgroups. RCS analysis revealed no significant nonlinear associations between the METS-IR, BRI and LBP. In the ROC analysis, METS-IR showed the highest area under the ROC curve in females, followed by BRI and BMI. Conclusions In conclusion, within a nationally representative sample of U.S. adults with low back pain, we identified significant positive correlations between METS-IR/BRI and LBP. These findings underscore the importance of maintaining healthy metabolic status, providing valuable insights for further research.